Kontribusi Administrasi Sumber Daya Manusia dalam Mendukung Proses Rekrutmen dan Pengelolaan Data Karyawan pada Divisi HRD di PT CNG Hilir Raya - Vania Putri Maharani; Nuzsep Almigo (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2026)
Human resources (HR) are strategic assets that play an important role in helping organizations achieve their objectives and maintain competitiveness in a dynamic industrial environment. This community service program was conducted using a participatory assistance approach at PT CNG Hilir Raya. The activities included observing partner needs, assisting with recruitment administration, managing applicant and employee documents and data, organizing health data, and preparing job lists. The results indicated that structured human resource administration helped support recruitment and employee data management. Activities such as document verification, systematic filing, data management, and job list preparation helped improve administrative efficiency and facilitate access to information for organizational needs. The program also provided practical experience in human resource administration, data management, and the use of Microsoft Excel, while supporting the development of communication, teamwork, time management, and adaptation skills in a professional work environment.